2014
DOI: 10.1038/sj.bdj.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance—the need for global solutions

Abstract: The causes of antibiotic resistance are complex and include human behaviour at many levels of society; the consequences aff ect everybody in the world. Similarities with climate change are evident. Many eff orts have been made to describe the many diff erent facets of antibiotic resistance and the interventions needed to meet the challenge. However, coordinated action is largely absent, especially at the political level, both nationally and internationally. Antibiotics paved the way for unprecedented medical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Antibiotic resistance genes (ARGs) are a product of microbial evolution and selection and are widely distributed in the natural environment, although usually in low abundance . The increasing abundance of ARGs at an unprecedented rate in our environment due to the intensive use of antibiotics is well documented and has aroused widespread public concern. , The emergence and widespread occurrence of antibiotic resistance genes have become a global threat to human health . Numerous studies have therefore been conducted to determine the abundance and composition of ARGs in multiple environments (e.g., soils, , rivers, landfill sites, municipal wastewater treatment plants, indoor dust, the phyllosphere of vegetables, animal faeces, and the gut of honey bees).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance genes (ARGs) are a product of microbial evolution and selection and are widely distributed in the natural environment, although usually in low abundance . The increasing abundance of ARGs at an unprecedented rate in our environment due to the intensive use of antibiotics is well documented and has aroused widespread public concern. , The emergence and widespread occurrence of antibiotic resistance genes have become a global threat to human health . Numerous studies have therefore been conducted to determine the abundance and composition of ARGs in multiple environments (e.g., soils, , rivers, landfill sites, municipal wastewater treatment plants, indoor dust, the phyllosphere of vegetables, animal faeces, and the gut of honey bees).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, antibiotics are widely used in animal husbandry to treat or prevent diarrhea and promote livestock growth (Brown et al, 2017). However, many studies have shown that the longterm use of antibiotics not only disrupts the normal community structure of animal gut microbes, but also increases the presence of disease and drug-resistant bacteria in the gut (Listed, 2014).In addition, cattle are food-producing animals, so residual antibiotics in the body may also seriously affect food safety and pose a great threat to human health (Zhang et al, 2019;Shao et al, 2021). Therefore, finding green and pollution-free antibiotics alternatives to prevent diarrhea in early weaned calves is crucial for animal husbandry development and food safety.…”
Section: Introductionmentioning
confidence: 99%